Victorian labour history : experience, identity and the politics of representation - Host, John, 1946- (London ; New York : Routledge, 1998)
Orthodox historical accounts of popular experience in mid-Victorian Britain suggest certain homogenous and seemingly clear stable social and political orders. Host re-examines the historical debate and challenges conventional interpretations.
Book Cover; Title; Contents; Acknowledgements; Introduction; Narratives of the past or histories of the present?; Social identity and the representation of experience; Who are 'the people' in mid-Victorian labour history?; Narrative history and the politics of exclusion; Afterword; Appendix: Evidence of witnesses in the cases of William Pearce and James Bristol; Notes; Bibliography; Index.
Includes bibliographical references (pages 256-272) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Labour Party (Great Britain) -- History; Labour Party (Great Britain); Working class -- Political activity -- Great Britain -- History -- 19th century; Labor movement -- Great Britain -- History -- 19th century; Representative government and representation -- Great Britain -- History -- 20th century; Chartism -- History; Travailleurs -- Activité politique -- Grande-Bretagne -- Histoire -- 19e siècle.; Mouvement ouvrier -- Grande-Bretagne -- Histoire -- 19e siècle.; Gouvernement représentatif -- Grande-Bretagne -- Histoire -- 20e siècle.; Chartisme -- Histoire; POLITICAL SCIENCE -- Political Process -- Political Advocacy; Chartism; Labor movement; Representative government and representation; Working class -- Political activity; Great Britain; 1800-1999; Electronic books; History